HUBUNGAN PENGETAHUAN PEGAWAI DENGAN PEMILAHAN LIMBAH PADAT DI RUMAH SAKIT UMUM SEMBIRING TAHUN 2019 - Yunita Syahputri Damanik; Khoirul Bahri (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2020)
Medical activities in the polyclinic room, ward, operating theatre and laboratory. The danger that comes from hospital medical waste which causes disease or injury. Medical waste exposure especially sharp object which causes virus infection like Human Immunodeficiency Virus (HIV)/Acquired Immuno Defeciency Syndrome(AIDS) and hepatitis B and C, who are at higher risk of infection because contamined sharp objects are nurses. This research done at the Sembiring Hospital Delitua Deli Serdang Regency. The objectives of this research is to know the relationship of the employees with the sorting of the medical solid waste. The design of this study was survey analytics design with a cross sectional study. The Univariate and bivariate of this research used Chi Square Test. The population of this research is nurses and the total sample is 65 people with the purposive sampling tehnic. The deficient of respondents knowlegde with the sorting of the medical solid waste as much as 35 people (53,8%). The sufficient of respondents knowlegde with the sorting of the medical solid waste as much as 16 people (24,6%) and the good knowlegde as much as 14 people (21,5%). The resulted of the bivariate analitycs with the knowlegde obtained p value 0.004< α 0.05, there is a relationship of employees knowlegde with the sorting of the medical solid waste, it is expect from the hospital to provide periodic checks in the medical waste producing ward to realize the comfort and cleanliness of the hospital environment.